2002
DOI: 10.1001/archotol.128.8.936
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal Endoscopic Treatment of Choanal Atresia Without Prolonged Stenting

Abstract: Transnasal endoscopic repair of CA is a safe and successful technique. The use of powered instrumentation and routine postoperative revision endoscopy seems to avoid prolonged nasal stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 19 publications
5
67
1
4
Order By: Relevance
“…This rate is very good compared with the reported rates of 75% (of eight patients) [3] and 80% [18] (of 40 patients) for the endoscopic transnasal technique. Schoem [20] had no cases of restenosis, but 78% of his patients required removal of granulation tissue with a microdebrider 3-4 weeks after surgery.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This rate is very good compared with the reported rates of 75% (of eight patients) [3] and 80% [18] (of 40 patients) for the endoscopic transnasal technique. Schoem [20] had no cases of restenosis, but 78% of his patients required removal of granulation tissue with a microdebrider 3-4 weeks after surgery.…”
Section: Discussionsupporting
confidence: 55%
“…More recently, Lazar and Younis [17], using transnasal endoscopy with conventional instruments, reported two failures, both in newborns with BCA. Therefore, this technique was assumed to be suitable for older children with UCA [18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the results after transnasal surgery are comparable to those after transpalatal surgery [1], although the latter is associated with greater blood loss, longer operating time and a more prolonged recovery [2]. For the choice of surgical instruments there are no comparative data, and drills [3][4][5], microdebriders [6][7][8] and lasers [9,10] all have their advocates.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence regarding Mitomycin C (an anti-neoplastic agent which inhibits fibroblasts and angioneogenesis, and therefore reduces granulation tissue formation and subsequent fibrosis) consists of small case series [8,11] and a single small comparative study (not blinded or randomised) which suggests possible benefit [12]. The use of stents is advocated by some [3][4][5]7,[12][13][14], and avoided by others [6,8,15].…”
Section: Introductionmentioning
confidence: 99%
“…La resección cuidadosa de la porción posterior del septum reduce la necesidad de proteger la mucosa para evitar la formación de tejido de granulación y sinarquías. Van Den Abbeele et al [15] han utilizado en sus pacientes el taponamiento nasal durante solo 2 días tras la cirugía y según sus conclusiones el taponamiento nasal no es necesario. Los resultados de la cirugía endoscopia en la atresia de coanas van desde un 75 a un 85% de éxitos según los diferentes autores [16,17].…”
Section: Discussionunclassified